2014
DOI: 10.1111/ctr.12404
|View full text |Cite
|
Sign up to set email alerts
|

The cell composition of infused donor lymphocyte has different impact in different types of allogeneic hematopoietic stem cell transplantation

Abstract: Donor lymphocyte infusion (DLI) is often used to enhance the graft‐versus‐leukemia (GVL) effect after allogeneic hematopoietic stem cell transplantation (allo‐HSCT). In this study, we first evaluated the impact of the cell composition of a modified DLI (mDLI) on the prognoses of patients. A total of 194 patients undergoing allo‐HSCT were enrolled and received mDLI for various clinical reasons. The infused cellular components of the mDLI were examined by flow cytometry. The results showed that infusion with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Meanwhile, this study points a new direction for the development of cellular therapies by manipulating the components of infused cells. 104 …”
Section: Gvhd and Gvl After DLImentioning
confidence: 99%
“…Meanwhile, this study points a new direction for the development of cellular therapies by manipulating the components of infused cells. 104 …”
Section: Gvhd and Gvl After DLImentioning
confidence: 99%
“…However, a greater number of CD14+ cells was an independent risk factor for II-IV aGvHD (HR = 1.758, p = 0.034) in haploidentical allo-SCT. These data show that the cell composition of DLI provides a novel approach for the development of cellular therapies by manipulating the components of infused cells [58].…”
Section: Biology Of Therapeutic DLImentioning
confidence: 78%
“… 11 In a study by Zhao et al of 194 patients undergoing allo-HSCT, the patients received mobilized DLI for various clinical reasons and the results showed that infusion with a dose of CD14-positive cells at greater than the 50th percentile was associated with a lower incidence of hematological relapse and longer disease-free survival after mobilized DLI. 5 …”
Section: Strategies and Treatment Options For Relapsed All Following mentioning
confidence: 99%
“… 1 For patients with ALL who relapse after allo-HSCT, the treatment options are limited and the clinical course and prognostic factors affecting outcome have not been well characterized. 2 , 3 Although a better understanding of the graft-versus-tumor/graft-versus-leukemia (GVL) effect, 4 minimal residual disease (MRD), and donor leukocyte infusions (DLIs) 5 have been achieved in recent decades, predicting ALL relapse after allo-HSCT and finding strategies to overcome ALL relapse remain critical to clinical practitioners. The aim of this article is to review the current concepts regarding risk factors, prevention, and treatment of ALL relapse following allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%